Pedagogical Orientations and Evolving Responsibilities of Technological Universities: A Literature Review of the History of Engineering Education - Martin, Diana Adela; Bombaerts, Gunter; Horst, Maja; Papageorgiou, Kyriaki; Viscusi, Gianluigi (Science and engineering ethics, 2023)
Current societal changes and challenges demand a broader role of technological universities, thus opening the question of how their role evolved over time and how to frame their current responsibility. In response to urgent calls for debating and redefining the identity of contemporary technological universities, this paper has two aims. The first aim is to identify the key characteristics and orientations marking the development of technological universities, as recorded in the history of engineering education. The second aim is to articulate the responsibility of contemporary technological universities given their different orientations and characteristics. For this, we first provide a non-systematic literature review of the key pedagogical orientations of technological universities, grounded in the history of engineering education. The five major orientations of technological universities presented in the paper are technical, economic, social, political, and ecological. We then use this historical survey to articulate the responsibilities of contemporary technological universities reflecting the different orientations. Technological universities can promote and foster the development of scientific, professional, civic, legal, or intra- and inter- generational responsibility. We argue that responsibility is not specific to any particular orientation, such that the concept is broadened to complement each orientation or mix of orientations of a technological university. Our contribution thus serves as a call for technological universities to self-reflect on their mission and identity, by offering a lens for identifying the orientations they currently foster and making explicit the responsibility arising from their current orientation or the ones they strive to cultivate.